2004
DOI: 10.1074/jbc.m406395200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Regulates KSR1 Stability, ERK Activation, and Cell Proliferation

Abstract: Kinase suppressor of Ras (KSR) is a molecular scaffold that interacts with the components of the Raf/MEK/ERK kinase cascade and positively regulates ERK signaling. Phosphorylation of KSR1, particularly at Ser 392 , is a critical regulator of KSR1 subcellular localization and ERK activation. We examined the role of phosphorylation of both Ser 392 and Thr 274 in regulating ERK activation and cell proliferation. We hypothesized that KSR1 phosphorylation is involved in generating signaling specificity through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 45 publications
(61 reference statements)
4
53
1
Order By: Relevance
“…Reconstitution experiments of KSR1 knockout cells with increasing amounts of transfected KSR1 showed that ERK activation became maximal when KSR1 was overexpressed ϳ14 fold above endogenous levels. However, even under these optimal conditions Ͻ5% of MEK and ERK were bound to KSR1 (30). This example shows that even small changes in the efficiency of an activation step within the Raf-MEK-ERK kinase cascade can translate into a strong effect on ERK activity.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstitution experiments of KSR1 knockout cells with increasing amounts of transfected KSR1 showed that ERK activation became maximal when KSR1 was overexpressed ϳ14 fold above endogenous levels. However, even under these optimal conditions Ͻ5% of MEK and ERK were bound to KSR1 (30). This example shows that even small changes in the efficiency of an activation step within the Raf-MEK-ERK kinase cascade can translate into a strong effect on ERK activity.…”
Section: Discussionmentioning
confidence: 99%
“…To further substantiate the above observation, we examined the phosphorylation status of ERK in both the cell lines. ERK (or p42/44MAPK) is phosphorylated by the sequential activation of RAF1 and MEK1/2, thereby inducing cell survival and proliferation (Razidlo et al 2004). It has been reported that ERK signaling downregulates the expression of anti-apoptotic proteins and promotes survival of pancreatic cancer cells (Boucher et al 2000).…”
Section: Alteration In Expression Of Cyclin D1 By High Glucose and Inmentioning
confidence: 99%
“…9,10 In vivo, deletion of Ksr1 inhibits Ras signaling-dependent tumor development in the mammary gland and skin. 8,11 However, there are incongruous data that Ksr1 can promote fibroblast proliferation, 12 but also that deletion of Ksr1 increases spontaneous immortalization and RasV12-induced proliferation of fibroblasts. 10 Therefore, Ksr1 has a critical function in modulating Ras pathway signaling, but its role in the cellular processes linked to transformation and in tumorigenesis remain incompletely resolved.…”
mentioning
confidence: 99%